Effectiveness of Using the Parkir-Go Application From the Perspective of Market Parking Attendants as an Increase Original Local Government Revenue - Anjani, Alya Emaniar; Rochmat Aldy Purnomo; Yeni Cahyono; Asis Riat Winanto; Choirul Hamidah (SEAN Institute, 2024)
This research analyzes the effectiveness of using the Parkir-Go application from the perspective of market parking attendants as an effort to increase Original Local Government Revenue in Ponorogo Regency, East Java. Parkir-Go is an application used to support the implementation of electronic parking in Ponorogo Regency. The method used in this research is descriptive quantitative using data collection techniques consisting of time series data on the realization of Ponorogo Regency market parking levies from 2018-2023 and documentation. To assess the effectiveness of electronic parking with the Parkir-Go application using indicators of accuracy of program targets and achievement of program objectives. The research results show that the use of the Parkir-Go application is less effective in increasing the Original Regional Income of Ponorogo Regency.